Réponses

2013-12-29T19:25:12+01:00
Bonsoir,

1) (x - 3)² - (2 - 5x) (x - 3) = (x² - 6x + 9) - (2x - 6 - 5x² + 15x)
(x - 3)² - (2 - 5x) (x - 3) = x² - 6x + 9 - 2x + 6 + 5x² - 15x
(x - 3)² - (2 - 5x) (x - 3) = 6x² - 23x + 15

2) 6x² - 23x +15 = 6x² - 23x +15

3) (x - 3) (6x - 5) = 6x² - 5x - 18x + 15
(x - 3) (6x - 5) = 6x² - 23x + 15
Meilleure réponse !
2013-12-29T19:49:33+01:00
1) (x-3)²-(2-5x) (x-3)
=x²-6x+9-(2x-6-5x²+15x)
=x²-6x+9-2x+6+5x²-15x
=6x²-23x+15

2)6x² - 23x +15
est déjà developpée

3)(x-3) (6x-5)
=6x²-5x-18x+15
=6x²-23x+15